Umbilical cord mesenchymal stem cell-derived exosomes promote wound healing and skin regeneration via the regulation of inflammation and angiogenesis - Yang, Yulin; Huang, Yinfu; Yang, Jian; Hu, Zhiwei; Wu, Shiduo; Yuan, Qian; Meng, Shuo; Li, Duanduan; Jiang, Meiling; Liao, Yan; Cai, Cheguo (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionWound healing and skin regeneration have become global health challenges, causing substantial harm to the physical and mental health. Many studies have shown that human umbilical cord mesenchymal stem cell-derived exosomes (hUCMSC-Exos) can promote tissue repair and regeneration. However, the efficacy and underlying mechanisms of hUCMSC-Exos in treatment remain to be elucidated.MethodshUCMSC-Exos were isolated by ultracentrifugation and characterized by analyses of nanoparticle tracking analysis (NTA), western blotting (WB), and transmission electron microscopy (TEM). The efficacy of hUCMSC-Exos on the proliferation, migration, and angiogenesis potential of fibroblasts and endothelial cells were examined in vitro. The effects of the hUCMSC-Exos on wound healing were assessed by wound closure rate, histological and immunohistochemical analyses. miRNAs and their target genes that may play a role in skin repair and regeneration were identified and predicted through bioinformatics analysis.ResultsIn vitro analysis indicated that hUCMSC-Exos are easily internalized by human umbilical vein endothelial cells (HUVECs) and human skin fibroblasts (HSFs), significantly promoting the proliferation and migration of HSFs, as well as the proliferation and tube formation of HUVECs. Analysis of skin wound models indicated that hUCMSC-Exos significantly accelerate wound healing by reducing inflammation, stimulating angiogenesis, and promoting the formation of extracellular matrix. Mechanistically, bioinformatics analysis suggests that Unc-51-like autophagy activating kinase 2 (ULK2), Collagen Type XIX Alpha 1 Chain (COL19A1), and Interleukin-6 Signal Transducer (IL6ST) are potential key molecules involved in the regulation of wound repair by hUCMSC-Exos.DiscussionIn summary, hUCMSC-Exos regulate the functions of HUVEC and HSFs through miRNA, significantly promoting wound healing and tissue repair, suggesting that hUCMSC Exos therapy is a promising therapeutic approach.